Design of Wireless Computer Network Infrastructure in Implementation of Kemendikbud Distributed Information Systems in Singingi Kuantan Islamic University - M. Hasim Siregar (Institute of Computer Science (IOCS), 2020)
The development of an integrated computer network is very important for the purpose of this research is to be able to build and monitor the performance and computer network of the Kuantan Singingi Islamic University (UNIKS) specifically for the lecturer LAN network which is connected to the SISTER RISTEKDIKTI local server on the UNIKS campus which has been built on the Cisco Packet Tracer simulator. and airLink simulation, this computer network design will use Wireless Media as an Access Point in each unique building so that each lecturer can access Sister without having to go to the admin sister psd who is in bakasi. The beginning of this research by means of storing the situation for access to the special computer network for sisters is very limited, the use of computer networks has not been maximized because the computer network infrastructure of Sister UNIKS is only found in the BAKASI-UNIKS building and can be accessed in that building. In carrying out the process of analyzing and designing Sister's computer network infrastructure using the Network Development Life Cycle (NDLC) Method. Lecturers and several stakeholders at the Kuantan Singingi Islamic University psd Sister in developing Computer Network Infrastructure are very supportive of integrating all existing buildings in the UNIKS environment for the purposes of Lecturer Certification carried out at the Ministry of Education and Culture SISTER